1994
DOI: 10.1021/ma00098a050
|View full text |Cite
|
Sign up to set email alerts
|

Poly(di-n-propylsilylene) and poly(diethylsilylene-co-di-n-propylsilylene): solid state structure and phase transitions

Abstract: Poly(di-n-propylsilylene) and poly(diethylsilylene-co-di-n-propylsilylene) have been investigated by Raman, IR, and UV spectroscopy, TGA, DSC, wide angle X-ray diffraction, and solid state l8C and MSi NMR. No IR-Raman coincidences were found in the Si-Si or Si-C stretching regions for (n-Pr2Si)", demonstrating that the main chain has a planar all-trans configuration, T" consistent with the UV absorption at 355 nm. From the Si-C stretching bands, all of the n-propyl groups appear to have the same conformation.(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…52,53 In accord with Ref. 5, their Raman spectra, provided that they are excited in the usual way by visible light, should exhibit pre-resonant behavior.…”
Section: S-s Conjugationmentioning
confidence: 56%
See 1 more Smart Citation
“…52,53 In accord with Ref. 5, their Raman spectra, provided that they are excited in the usual way by visible light, should exhibit pre-resonant behavior.…”
Section: S-s Conjugationmentioning
confidence: 56%
“…The vibrational spectra of both polymers along with the band assignments were published previously. 52,53 The assigned Raman spectra of silicon five-membered rings can be found in Refs 54 and 55.…”
Section: S-s Conjugationmentioning
confidence: 99%
“…A change in the silicon backbone conformation can be followed most easily by the UV method. In addition, the selection rules operating in the n(SiSi) and n(SiC) regions of the Raman and IR spectra allow determination of the symmetry of the polymer repeating unit and thus the polymer backbone structure [6][7][8][9]13] (see Fig. 2).…”
Section: The Approaches Usedmentioning
confidence: 99%
“…The aim of this paper is to describe characteristic features of polydi-n-alkylsilane transitions based on generalization from the authors' experience [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and literature data, as well as to demonstrate that the three types of ordering are not necessarily interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the copolymers with DM/MP = 7/3-9/1 forms a columnar mesophase at elevated temperatures, as was reported for some other polydialkylsilanes. [9][10][11][12][13][14] We showed that the highly oriented materials of insoluble polysilanes could be prepared by extrusion in the columnar mesophase and that the mechanical properties of oriented PMMMP rods were improved with increasing degree of orientation. [7] It was further shown that the modulus at room temperature decreased with increasing content of MP units, suggesting that the molecular motion of the longer substituents lowers the modulus at room temperature.…”
Section: Introductionmentioning
confidence: 96%